A methods engineering study on Sun King Electronics Company, Incorporated - Atuli, Marian; Borromeo, Levy Martin; Tolentino, Trixie Jemavi (Diliman, Quezon City College of Engineering, 2004)
With increasing competition and economic difficulties, the best hope of any industry is improving its productivity. A well-executed methods engineering study is needed to achieve considerable improvements in productivity. In accordance to this, a methods engineering study was conducted in Sun King Electronics Co., Inc. a manufacturer of inductor coil for colored television sets. The scope of the study lies within one specific production line, Line B, manufacturer of various transformer types. The production of two transformer types, TLN1098AH and TLN2220, was the focus of the study. The importance of the general welfare of the worker was also taken into consideration in the course of the study. Another underlying principle of the study is to present to the company a 'better way of doing things' without adding costs but to cut costs instead. The present production system in Line B was documented in detail. The documentation consists of the production systems framework, organizational structure, production materials and operations, plant layout, work design and system and procedures. A close examination on the processes involved in the manufacture of the transformers helped the team identify significant factors that can be used in further study. Problem identification and analysis follow the documentation of the present system. The problems were rationalized and their causes were traced. The problems were segregated into two groups : core problems and secondary problems. The core problems or the major problems were the ones addressed by the team in the generation of alternatives. The secondary problems were those rooted in the core problems. Therefore, the alternative solutions for the core problems also serve the secondary problems. In the generation of alternatives, the "must" and the "wants" objectives wre first identified. A decision analysis procedure follows wherein the recommendations of the group were presented. The recommendations of the team include a new layout, line balancing, standardizing worker motions, and highly improved working conditions. In the selection of the best method, various constraints associated with each alternative were considered. These recommendations, when implemented strictly, will result to considerable increase in productivity of the whole line. The efficiency of each worker is also expected to improve. Through this study, the Sun King Electronics Co., Inc. is given an opportunity to, not just increase, but optimize its productivity.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis